1996
DOI: 10.1128/aem.62.7.2201-2211.1996
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale studies of factors related to coliform regrowth in drinking water

Abstract: An 18-month survey of 31 water systems in North America was conducted to determine the factors that contribute to the occurrence of coliform bacteria in drinking water. The survey included analysis of assimilable organic carbon (AOC), coliforms, disinfectant residuals, and operational parameters. Coliform bacteria were detected in 27.8% of the 2-week sampling periods and were associated with the following factors: filtration, temperature, disinfectant type and disinfectant level, AOC level, corrosion control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
197
2
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(212 citation statements)
references
References 34 publications
8
197
2
5
Order By: Relevance
“…A minimum concentration of 100 mg AOC app l -1 was needed by Vibrio cholerae O1 to grow in natural freshwater . Correspondingly, a significant negative correlation between the occurrence of coliforms in drinking water systems and AOC concentrations lower than 100 mg l -1 was reported (LeChevallier et al, 1996). It seems that also for E. coli O157 a certain threshold value of AOCapp for growth exists.…”
Section: Discussionmentioning
confidence: 86%
“…A minimum concentration of 100 mg AOC app l -1 was needed by Vibrio cholerae O1 to grow in natural freshwater . Correspondingly, a significant negative correlation between the occurrence of coliforms in drinking water systems and AOC concentrations lower than 100 mg l -1 was reported (LeChevallier et al, 1996). It seems that also for E. coli O157 a certain threshold value of AOCapp for growth exists.…”
Section: Discussionmentioning
confidence: 86%
“…Free chlorine concentrations decreased from 0.47 mg/L in water leaving the treated surface water supply point to concentrations at or near the detection limit (0.02 mg/L) at the house. It has been reported that significant growth of total coliforms occurs in water when the free chlorine concentrations are less than 0.2 mg/L (LeChevallier et al, 1996). Measured free chlorine levels in the distribution system and at the household level (i.e., cisterns and storage tanks) are one tenth of that value.…”
Section: Discussionmentioning
confidence: 99%
“…Various field studies have shown that significant bacterial growth can occur in water of 15°C or higher (Donlan et al, 1994;Smith et al, 1989;Donlan & Pipes, 1988;Fransolet et al, 1985). LeChevallier et al (1996) found that coliform bacteria occurred more frequently and in higher concentrations at water temperatures > 15°C. That study also observed an 18-fold increase of coliforms in chlorinated systems when temperatures were increased from 5°C to > 20°C.…”
mentioning
confidence: 99%
“…USEPA surface water treatment rules state that heterotrophic plate counts (HPC) should be no more than 500 CFU/ ml (U.S. Environmental Protection Agency 1989). Prokaryotic and eukaryotic microorganisms that are present in water leaving the treatment plant, though probably inactivated by the disinfection process, may recover and grow in water distribution system (WDS) biofilms (LeChevallier et al 1996). Sections of biofilms in distribution systems can periodically break off and enter the bulk water (Daly et al 1998;Stoodley et al 2002).…”
Section: Introductionmentioning
confidence: 99%